MiR-30a and miR-379 modulate retinoic acid pathway by targeting DNA methyltransferase 3B in oral cancer - Shiah, Shine-Gwo (J Biomed Sci, 2020)
BACKGROUND: Epigenetic silencing of retinoic acid (RA) signaling-related genes have been linked with the pathogenesis and clinical outcome in oral squamous cell carcinoma (OSCC) carcinogenesis. However, the precise mechanisms underlying the abnormal silencing of RA signaling-related genes in OSCC have not been well investigated. METHODS: Using combined analysis of genome-wide gene expression and methylation profile from 40 matched normal-tumor pairs of OSCC specimens, we found a set of retinoid signaling related genes are frequently hypermethylated and downregulated in OSCC patient samples, including alcohol dehydrogenase, iron containing 1 (ADHFE1) and aldehyde dehydrogenase 1 family, member A2 (ALDH1A2), which are the important rate-limiting enzymes in synthesis of RA. The expression of ADHFE1 and ALDH1A2 in OSCC patients was determine by quantitative real-time PCR (qRT-PCR) and immunohistochemistry. The binding sites of miR-30a and miR-379 with DNA methyltransferase 3B (DNMT3B) were predicted using a series of bioinformatic tools, and validated using dual luciferase assay and Western blot analyses. The functions of miR-30a, miR-379, and DNMT3B were accessed by growth and colony formation analyses using gain- and loss-of-function approaches. Chromatin immunoprecipitation (ChIP) was performed to explore the molecular mechanisms by arecoline and 4-(methylnitrosamino)-1-(3-pyridyl)-1-butanone (NNK) treatment. RESULTS: We demonstrated that deregulated miR-30a and miR-379 could represent a mechanism for the silencing of ADHFE1 and ALDH1A2 in OSCC through targeting DNMT3B. Ectopic expression of miR-30a and miR-379 could induce re-expression of methylation-silenced ADHFE1 and ALDH1A2, and lead to growth inhibition in oral cancer cells. Furthermore, the dysregulation of the miRNAs and DNMT-3B may result from exposure to tobacco smoking and betel quid chewing. CONCLUSIONS: Our results demonstrate that tobacco smoking and betel quid chewing could repress miR-30a and miR-379, which upregulate the DNMT3B expression, in turn, lead to the hypermethylation of ADHFE1 and ALDH1A genes, consequently, promote the oncogenic activity. These findings highlight the potential use of retinoids in combination with epigenetic modifiers for the prevention or treatment of oral cancer.